2018
DOI: 10.1016/j.clnesp.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Home Parenteral Nutrition on the lives of adults with Type 3 Intestinal Failure

Abstract: The study illustrates how patients' lives are affected by HPN. Statements generated from this qualitative study were used to produce the Parenteral Nutrition Impact Questionnaire (PNIQ), a patient-centric measure of quality of life specific to people using HPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 22 publications
2
31
0
10
Order By: Relevance
“…7,30,35 Other pub-lished QoL data are primarily based on qualitative interviews with open questions, rendering meaningful, quantitative cross-comparison difficult. 37,38 Therefore, this is 1 of the largest structured, quantitative QoL studies in PNdependent adults with IF published to date that showed an association between determinants of QoL such as citrulline levels, presence of ostomy, and oral intake status and 4 of 10 SF-36 categories by multivariable analyses (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…7,30,35 Other pub-lished QoL data are primarily based on qualitative interviews with open questions, rendering meaningful, quantitative cross-comparison difficult. 37,38 Therefore, this is 1 of the largest structured, quantitative QoL studies in PNdependent adults with IF published to date that showed an association between determinants of QoL such as citrulline levels, presence of ostomy, and oral intake status and 4 of 10 SF-36 categories by multivariable analyses (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…HPN is experienced in the context of living with other symptoms of illness, which may be burdensome [8,26,28]. Other recurring themes are restrictions imposed from being connected to the HPN and the lack of autonomous control over their body [8,26,29]. Moving about with the feed was particularly problematic for frailer patients.…”
Section: Discussionmentioning
confidence: 99%
“…All needs-based PROMs contain items derived directly from patients, as they are the only people who could be considered "experts" in living with a specific disease 21,22 . A crucial aspect of these PROMs is that, while the items are all generated directly from relevant interviewees, selection of those to be included in the questionnaires is governed by the conceptual model.…”
Section: The Needs-based Quality-of-life (Qol) Theory Modelmentioning
confidence: 99%